MENUMBUHKAN SEMANGAT UNTUK BELA NEGARA BAGI WARGA KELOMPOK PKK KELURAHAN KALICARI, KECAMATAN PEDURUNGAN, KOTA SEMARANG - Muzayanah Muzayanah (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The Unitary State of the Republic of Indonesia (NKRI) is an independent state that was proclaimed on August 17, 1945. As an independent country, the Indonesian state has the right to regulate and administer the state administration system of the Republic of Indonesia based on the state constitution, namely the 1945 Constitution. To maintain an independent Indonesian state, the concern of all Indonesian citizens is needed so that this country continues to develop and progress as aspired in the fourth paragraph of the preamble to the 1945 Constitution. Awareness in the nation and state must be realized by practicing State Defense and love for the country in the container of the unitary state of the Republic of Indonesia, so that the we remain a prosperous, just and prosperous country based on Pancasila and the 1945 Constitution. State Defense is a form of public awareness to participate in maintaining security in their respective environments according to their respective capacities and professions. Defending the State can be done by maintaining the safe situation of each family and carrying out its activities as the smallest unit of society in a country. Furthermore, the question is whether the people of Kalicari Village, Pedurungan District, Semarang City in general already know about what is meant by State Defense ?. It turns out that there are still many people who don't know or even don't understand what is meant by State Defense. When asked about State Defense, most answered that what was meant by State Defense was a way to face the enemy in the event of war, so it was often understood that they had to take up arms to fight against the enemy. Apart from that, after we were implementing this Unisbank legal education, we asked the community and PKK group of Kalicari Village, Pedurungan District, Semarang City about whether they had known about State Defense? In fact, most of them do not know and understand what is meant by State Defense. Based on this fact, we implementers of Community Service activities have a program to provide education on how to generate the spirit of State Defense for the citizens of this PKK group, so that it is hoped that they will be able to cultivate a sense of love for the country and State Defense for this independent Indonesia. Given the very importance of education about State Defense, so that the community, especially the residents of Kalicari sub-district, Pedurungan sub- district, Semarang City knows and understands so it is hoped that knowing and understanding State Defense will make people more aware of the importance of unity and integrity in living as a society, nation and state. in implementing State Defense in accordance with the profession or expertise in their respective fields.